Carcass, meat and fat quality in Italian Merino derived lambs obtained with 'organic' farming systems - Morbidini L.; Sarti D.M.; Pollidori P.; Valigi A. (Production systems and product quality in sheep and goats, 2001)
The quality of carcass, meat and intramuscular fat was evaluated in thirty-two, 75 day-old, Italian Merino derived lambs produced using a certified organic farming system. At the same time 16 lambs from the same farm were weaned at 40 days of age and reared traditionally with hay plus concentrate until 75 days and then slaughtered. Carcasses were classified with the SEUROP and bis-grid EU systems. Dressing percentage, Longissimus dorsi physical and chemical characteristics and fatty acid composition of intramuscular fat were determined. The results differed between 'organic' and 'traditional' lambs in both carcass, meat and fat quality.
Meeting of the Sub-Network on Production Systems of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Sheep and Goats, 1999/09/23-25, Molina de Segura-Murcia (Spain)